Visus iste non a carne trahebatur. Rola zmysłów w kontemplacji w księdze VII i IX "Wyznań" Augustyna - Stróżyński, Mateusz (Vox Patrum, 2013)
The purpose of the paper is to examine the role of the senses in contemplation in Book Seven and Nine of Augustine’s Confessions. The bishop of Hippo’s conception of contemplation is deeply influenced by Plotinus, especially in the early period, and this influence is present e.g. in the distiniguishing of two forms of contemplation: the one in which all sensible objects are eliminated from awareness and the one in which they are present or used as a medium of contemplation. A method which leads to contemplation in which the senses are completely absent is the Plotinian method of „agnoetic meditation”. The method appears in Augustine as well, both in Book Seven and Book Nine. The forms of the contemplation of God, which are described there, do not involve the senses, and their sole object is God. It generates a paradoxical situation especially in the vision of Ostia, where the „beyond body” contemplation is impossible to reconcile with the resurrection of the body and seeing God in the body. Augustine does not solve the paradox which is of a great importance, since it shows the tension between Platonic philosophy and Christian revelation.